Preliminary study of sulphide removal using ion exchange resin - Syarifah, Abd Rahim; Teo, Kai Li (Elsevier Ltd, 2018)
The paper presents the investigation of sulphide removal via ion exchange resin. Sulphidic spent caustic (SSC) is a dark brown to black effluent generated from petrochemical and oil refinery industries. Typically, SSC has a pH of 13-14, and sulphide concentration of 0.5-4.0wt%. The large amount of sulphide content in SSC leads to its toxic property, obnoxious odor and hazardous nature. This will threaten health and safety of workers, and may pollute the environment. The SSC may not be discharged to wastewater treatment facilities untreated as the high sulphide content will cause corrosion in the pipes especially in aqueous condition. In fact, the Malaysia Department of Environment has limited the acceptable sulphide discharge in industrial effluent at 0.5 mg/L as stated in the Environmental Quality (Industrial Effluent) Regulation 2009. Hence, it is desirable to remove sulphide in the SSC. This research focused on the removal of sulphide from synthetic SSC via strongly basic anion exchange resin. A synthetic SSC was simulated to represent the SSC. The static method was applied, where the synthetic SSC was allowed to stay in a column of resin for several retentions time. The synthetic SSC was characterised for its sulphide content, chemical oxygen demand (COD) and pH before and after the treatment in order to analyse the effect of ion exchange resin treatment. The resin was also characterised for its moisture retention, exchange capacity, and pore size. The treatment was able to remove about 95.8% of the sulphide and the COD was reduced by 94.5%.